Metal-Halide Perovskite Semiconductors From Physical Properties to Opto-electronic Devices and X-ray Sensors - Nie, Wanyi; Iniewski, Krzysztof (Kris) (Springer International Publishing : Imprint: Springer, 2023)
VII, 348 p. 1 illus.